Assistive technology: a veritable tool in rehabilitating persons with special needs (2016)
Rehabilitation of persons with special needs requires holistic remediated and adjustment tools (strategies) which would accommodate the use of assistive, adaptive and rehabilitative devices, structurally designed to promote greater independence. These tools and strategies; commonly referred to as assistive technology would enable persons with special needs perform tasks that they were formerly unable to do or those ones they do with difficulty. Thus, comprehensive use of assistive technology provides the necessary enhancements to, or changing methods of interacting with the technology needed to accomplish any required task(s). Assistive technology would also enhance the process of rehabilitation and psycho-social adjustments as well as educational cum vocational performance of persons with special needs. Therefore, this paper highlights the kinds of rehabilitation options towards resolving the attendant educational, vocational and socio-emotional problems due to disabilities. The paper concludes with relevance of assistive technology as a veritable tool in rehabilitating persons with special needs. It also encourages comprehensive use of assistive technology as a complementary service-delivery mechanism in all the rehabilitation programmes and centres.